The possibilities of speech therapy stimulation in children with postponement of school attendance - Eva Vanousová (Ignatianum University Press, 2017)
Our report presents the Eľkonin´s training of phonematic awareness. This programme is suitable for 5-6 years old children or children whose compulsory school attendance is postponed. We are shortly presenting the results of our study that was done in 20 children. The aim of the study was to quantify and to compare the level of phonological abilities in the studied group of children before and after the training. We would like to show that it is a very suitable stimulating programme that is possible to apply in pre-school children with the impaired communication ability and the postponement of school attendance which can be the risk factors in the process of learning and reading. This training can be applied by special educationists, speech therapists and elementary school teachers after passing the course.